Additive manufacturing of star poly(ε-caprolactone) wet-spun scaffolds for bone tissue engineering applications. (July 2013) - Mota, Carlos; Puppi, Dario; Dinucci, Dinuccio; Gazzarri, Matteo; Chiellini, Federica
Three-dimensional fibrous scaffolds made of a three-arm star poly(ε-caprolactone) were developed by employing a novel computer-aided wet-spinning apparatus to precisely control the deposition pattern of an extruded polymeric solution as a filament into a coagulation bath. Star poly(ε-caprolactone)/hydroxyapatite composite scaffolds composed of fibres with a porous morphology both in the outer surface and in the cross section were successfully produced with a layer-by-layer approach achieving good reproducibility of the internal architecture and external shape. Changes in processing parameters were used to fabricate scaffolds with different architectural parameters in terms of average pore size in the xy- axes (from 190 to 297 µm) and in the z -axis (from 54 to 126 µm) and porosity (in the range of 20%–60%). Based on the mechanical characterization, processing variations and hydroxyapatite loading have an influence on scaffold compression properties. Cell cultures, using a murine pre-osteoblast cell line, had good cell responses in terms of proliferation and osteoblastic differentiation. Thus, this technique appears to be an effective method for producing customized polymeric scaffolds for bone tissue engineering applications.